Clinicopathological features and prognostic value of incidental prostatic adenocarcinoma in radical cystoprostatectomy specimens: a systematic review and meta-analysis of 13,140 patients - Fahmy Ahmed, Omar Ahmed; Mohd Ghani @ Mamat, Khairul Asri; Schubert, Tina; Renninger, Markus; Stenzl, Arnulf; Gakis, Georgios (American Urological Association, 2017)
Purpose: There is controversy in the literature about the oncologic significance of incidental prostate cancer detected at radical cystoprostatectomy for bladder cancer. Materials and Methods: An online search was done for studies reporting incidental prostate cancer in cystoprostatectomy specimens. After following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines we identified a total of 34 reports containing 13,140 patients who underwent radical cystoprostatectomy for bladder cancer with no previous history of prostate cancer. A cumulative analysis was performed on the available data regarding prevalence, clinicopathological features and oncologic outcomes. RevMan, version 5.3 was used for data meta-analysis. Results: Of the 13,140 patients incidental prostate cancer was detected in 3,335 (24.4%). Incidental prostate cancer was significantly associated with greater age (Z = 3.81, p = 0.0001, d = 0.27, 95% CI −0.14–0.68), lymphovascular invasion of bladder cancer (Z = 2.07, p = 0.04, r = 0.14, 95% CI 0.09–0.18) and lower 5-year overall survival (Z = 2.2, p = 0.03). Among patients with clinically significant and insignificant prostate cancer those with clinically significant prostate cancer significantly more frequently showed a positive finding on digital rectal examination (Z = 3.12, p = 0.002, r = 0.10, 95% CI 0–0.19) and lower 5-year overall survival (Z = 2.49, p = 0.01) whereas no effect of age was observed (p = 0.15). Of 1,320 patients monitored for biochemical recurrence prostate specific antigen recurrence, defined as prostate specific antigen greater than 0.02 ng/ml, developed in 25 (1.9%) at between 3 and 102 months. Conclusions: This meta-analysis suggests that incidental prostate cancer detected during histopathological examination of radical cystoprostatectomy specimens might be linked with adverse characteristics and outcomes in patients with invasive bladder cancer.